Compensating the cooperators: Is sorting in the prisoner's dilemma possible? - Iris Bohnet; Dorothea Kübler (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2000)
Choice between different versions of a game may provide a means of sorting, allowing players with different preferences to self-select into groups of similar types. We experimentally investigate whether auctioning off the right to play a prisoner's dilemma game in which the cost of unilateral cooperation is lower than in the status quo version separates (conditional) cooperators from money maximizers. After the auction, significantly more subjects cooperate in the modified PD than in the status quo PD whereas there is no difference between cooperation rates if the two versions of the game were assigned to participants. However, sorting is incomplete and cooperation deteriorates over time. The auction price does not correspond to the differences in expected values between the modified and the status quo game.
urn:nbn:de:kobv:11-10048536
Keywords: C72; 330; Auctions; Experiments; Prisoner's dilemma game; Sorting; Conditional cooperation